2018
DOI: 10.3389/fimmu.2018.00172
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the Reference Intervals of Lymphocyte Function in Healthy Adults Based on IFN-γ Secretion Assay upon Phorbol-12-Myristate-13-Acetate/Ionomycin Stimulation

Abstract: The function of lymphocytes is the key to reflect the immune status of hosts. Evaluation of lymphocyte function is a useful tool to monitor the effect of immunosuppressive treatment and predict the prognosis of immune-mediated diseases (e.g., cancer, autoimmune diseases, and infectious diseases). As the lymphocytes have various activities, such as activation, cytotoxicity, and cytokine secretion, it is a challenge to evaluate the function of lymphocytes in clinical practice and the reference intervals (RIs) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…Although macrophages are the main source of TNF-α (49), the production of this cytokine was also described for T-cells (46). A recent study, also aiming to establish a reference interval, reported the following proportions of activated cytokine-producing cells, compared with us: CD4+ 30% IL-2+ (vs. 61%), 25% TNF-α+ (vs. 27%), 23% IFN-γ+ (vs. 7%); together with CD8+ cells 3% IL-2+ (vs. 25%), 25% TNF-α+ (vs. 7%) and 43% IFN-γ+ (vs. 8%) (35). Such significant differences are very common between ICS protocols and, to a certain extent, between other flow cytometry experiments.…”
Section: Viability and Cytokine Synthesismentioning
confidence: 71%
See 1 more Smart Citation
“…Although macrophages are the main source of TNF-α (49), the production of this cytokine was also described for T-cells (46). A recent study, also aiming to establish a reference interval, reported the following proportions of activated cytokine-producing cells, compared with us: CD4+ 30% IL-2+ (vs. 61%), 25% TNF-α+ (vs. 27%), 23% IFN-γ+ (vs. 7%); together with CD8+ cells 3% IL-2+ (vs. 25%), 25% TNF-α+ (vs. 7%) and 43% IFN-γ+ (vs. 8%) (35). Such significant differences are very common between ICS protocols and, to a certain extent, between other flow cytometry experiments.…”
Section: Viability and Cytokine Synthesismentioning
confidence: 71%
“…Nevertheless, our subsequent experience with PBMC density gradient isolation (this study included) showed us that processing blood volumes higher than 3mL will in fact significantly lower the cell yield. Several concentrations of PMA/ION are reported in the literature for PBMC activation, ranging from 1 to 100ng/mL PMA (32-39) and from 0.4 to 1.4µM for ION (that is roughly 300-1000ng/ mL) (32)(33)(34)(35)(36)38), depending on protocol requirements and personal preferences. While the exact PMA concentration values seem to be chosen arbitrarily (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte function. PMA/ionomycin-stimulated lymphocyte function assay was performed as described in our previous studies (22,24). Briefly, 100 μL of whole blood was diluted with 400 μL of IMDM medium and stimulated with Leukocyte Activation Cocktail (containing PMA, ionomycin and brefeldin A, BD GolgiPlug) for 4 hours.…”
Section: Methodsmentioning
confidence: 99%
“…PMA/ionomycin-stimulated lymphocyte function assay was performed as described previously. [11] The percentages of IFN-γ positive cells in different cell subsets were defined as the function of them. The data were reviewed by a trained team of physicians in Tongji Hospital.…”
Section: Data Collectionmentioning
confidence: 99%